The elderly in the Venafrana reality. Results of a survey - Bucci, Sabina (Medicina e Morale, 2024)
The problem of the condition of the elderly has increasingly come to the attention first of scholars, then of politicians, to the point of becoming the dominant topic of national and international conferences, discussions, round tables, etc., but unfortunately remaining on a theoretical level and not descending, if not rarely, to the practical level of concreteness and operativeness.